2006
DOI: 10.1152/ajplung.00371.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled marijuana smoke disrupts mitochondrial energetics in pulmonary epithelial cells in vivo

Abstract: -Habitual marijuana smoking is associated with inflammation and atypia of airway epithelium accompanied by symptoms of chronic bronchitis. We hypothesized that ⌬ 9 -tetrahydrocannabinol (THC), the primary psychoactive component of marijuana, might contribute to these findings by impairing cellular energetics and mitochondrial function. To test this hypothesis, we examined particulate smoke extracts from marijuana cigarettes, tobacco cigarettes, and placebo marijuana (0% THC) cigarettes for their effects on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 31 publications
3
46
0
5
Order By: Relevance
“…The pattern of selective response to marijuana smoke extract relative to tobacco or placebo extracts was similar to the pattern observed previously for loss of Ψ m in A549 cells and in an in vivo smoke inhalation model (Sarafian et al, 2003;Sarafian et al, 2006). This similarity raised the possibility of a causal relationship between THC-mediated disruption of mitochondrial energetics and its effects on chemotaxis.…”
Section: Role Of Mitochondrial Injury In Thc-induced Chemotaxis Inhibsupporting
confidence: 82%
See 2 more Smart Citations
“…The pattern of selective response to marijuana smoke extract relative to tobacco or placebo extracts was similar to the pattern observed previously for loss of Ψ m in A549 cells and in an in vivo smoke inhalation model (Sarafian et al, 2003;Sarafian et al, 2006). This similarity raised the possibility of a causal relationship between THC-mediated disruption of mitochondrial energetics and its effects on chemotaxis.…”
Section: Role Of Mitochondrial Injury In Thc-induced Chemotaxis Inhibsupporting
confidence: 82%
“…In both primary human lung epithelial cells and the lung tumor cell line, A549, mitochondrial membrane potential (Ψ m ) is diminished along with cellular ATP level. We have also performed in vivo smoke inhalation studies with rats exposed to marijuana smoke and found reduced mitochondrial-pattern staining using the potentiometric probe, JC-1, suggesting that marijuana smoke may impair epithelial cell energetics in humans (Sarafian et al, 2006). These events do not occur upon exposure to tobacco smoke suggesting that marijuana smokers may be at risk of physiological impairment distinct from that of tobacco smokers.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…46 Thus, when taken together with apoC-III-mediated decreases in the rate of mitochondrial respiration, 47 the observed increases in apoC-III in the MJ users hint to the possibility that chronic MJ abuse could lead to impairments of cellular energetics and mitochondrial function, which are critical events associated to myocardial infarction, stroke and ischemic/reperfusion damage. 48 This discussion might offer a partial explanation for the chronic effects of the drug on cardiac and cerebrovascular systems. [49][50][51] The manner by which chronic MJ smoking might cause these increases in serum apoC-III levels remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Free radical generation both at receptor binding (S.T. Carney, North Carolina Central University, Durham, NC, USA; personal communication) and by mitochondrial uncoupling [4] has been demonstrated.…”
Section: Referencesmentioning
confidence: 99%